Open-Design Collar vs. Conventional Philadelphia Collar Regarding User Satisfaction and Cervical Range of Motion in Asymptomatic Adults. (April 2016) - Ghorbani, Faezeh; Kamyab, Mojtaba; Azadinia, Fatemeh; Hajiaghaei, Behnam
ABSTRACT: Supplemental digital content is available in the text. Objective: The current study aimed to compare the Philadelphia collar and an open-design cervical collar with regard to user satisfaction and cervical range of motion in asymptomatic adults. Design: Seventy-two healthy subjects (36 women, 36 men) aged 18 to 29 yrs were recruited for this study. Neck movements, including active flexion, extension, right/left lateral flexion, and right/left axial rotation, were assessed in each subject under three conditions—without wearing a collar and while wearing two different cervical collars—using a dual digital inclinometer. Subject satisfaction was assessed using a five-item self-administered questionnaire. Results: Both Philadelphia and open-design collars significantly reduced cervical motions ( P < 0.05). Compared with the Philadelphia collar, the open-design collar more greatly reduced cervical motions in three planes and the differences were statistically significant except for limiting flexion. Satisfaction scores for Philadelphia and open-design collars were 15.89 (3.87) and 19.94 (3.11), respectively. Conclusion: Based on the data of the 72 subjects presented in this study, the open-design collar adequately immobilized the cervical spine as a semirigid collar and was considered cosmetically acceptable, at least for subjects aged younger than 30 yrs.